Handbook of research on trends in the diagnosis and intervention of neurodevelopmental disorders - Gupta, Sanjeev Kumar, 1983-; Venkatesan, S., 1961-; Goswami, S. P. (Satpal P.), 1973-; Kumar, Rajeev (Professor of computer science & engineering) (Advances in medical technologies and clinical practice book series., 2019)
"This book discusses and disseminates contributions of recent trends in diagnosis, assessment and intervention techniques of neurodevelopmental disorders, with the goal of helping clinicians and determine its utility for the benefit of affected person and their caregivers"--Provided by publisher.